Regulating the d-band center of Ru/CoMoO4 ternary heterostructure by interface engineering for accelerated hydrogen adsorption kinetics - Miao Ma; Min Yang; Cai-Yue Zhang; Hai-Yi Sun; Rong-Jing Su; Xiao-Rui Yue; Chen-Xi Li; Yong-Ming Chai; Bin Dong (Fuel, 2026)

A low-molecular-weight glucan from Lycium barbarum reprograms tumor-associated macrophages involving the Dectin-1/NOX2 axis to suppress hepatoma - Yanping Cai; Yunliang Chen; Chunjing Li; Hongxu Chen; Yi Ji; Shaojie Zhang; Ying Zhu; Shuiling Cao; Rui Xu; Xueqian Xie; Qi Yi; Qing Wang; et al. (Carbohydrate Polymers, 2026)

Development of a bifunctional dynamic control system for effective product synthesis in Bacillus licheniformis DW2 - Yi Rao; Jiaqi Wang; Junyan Liu; Rui Zhao; Xin Ma; Dongbo Cai; Shouwen Chen (Bioresource Technology, 2026)

A review of atmospheric black carbon research progress in China - Qi Zhou; Shunyao Wang; Shujun Bie; Junjie Cai; Yingjun Chen; Yuan Cheng; Xiang Ding; Jianwei Gu; Jie Li; Weijun Li; Dantong Liu; Jiaying Liu; et al. (Atmospheric Environment, 2026)

Antioxidant Activity of Bioactive Peptides Derived from Ulva prolifera in HaCaT Cells and Zebrafish - Li-Ru Hong; Shuo-Qi Wang; Ting-Ting Wu; Zhi-Ru Chen; Mo Chen; Chun-Er Cai; Pei-Min He; Ya Zhao; Rui Jia (Marine Biotechnology, 2026)

Bioinspired superamphiphobic microreactor for efficient fabrication of cellulose nanocrystal photonic pigments - Kai Xiong; Jing Guo; Yingying Chen; Rui Tong; Yunjia Cai; Heng Xie; Ting Wu; Jinping Qu (Chemical Engineering Journal, 2026)

Research progresses on the regulatory roles of microRNAs in radiation-induced pulmonary fibrosis - Min Zhu; Haowei Li; Rui Chen; Jianming Cai; Tao Wang; Changjing Zuo (Journal of Molecular Histology, 2026)

Compartmental pH regulation in cancer and antitumor immunity: therapeutic opportunities and challenges - Fangquan Chen; Xiutao Cai; Qile Zhou; Zhen Huang; Jie Wang; Rui Kang; Daolin Tang; Jiao Liu (Apoptosis, 2026)

Unveiling the participation of microbiomes in the trait formation of economically important Pyropia haitanensis varieties - Yi Liu; Jingyi Wang; Qijun Luo; Juanjuan Chen; Rui Yang; Peng Zhang; Tiegan Wang; Huifeng Cai; Haimin Chen (Aquaculture, 2026)

Pancancer pro-angiogenic atlas unravels tumor-educated pericyte-augmented anti-angiogenic resistance - Yongqiang Zheng; Hui Sun; Zhe Fu; Haojie Chen; Guangyao Cai; Xin Huang; Yi-Qian Pan; Kai Yu; Ping Chen; Zhuoran Liang; Junteng Li; Jiamin Hu; et al. (Science Bulletin, 2026)

Fabrication of Fe-Cu bimetallic particle electrodes from copper slag and biochar for enhanced levofloxacin degradation: Performance, mechanism, and toxicity assessment - Jiao Wei; Linjin Li; Guangfei Qu; Rui Xu; Junyan Li; Yingying Cai; Minghua Chen; Xinxin Liu; Xiaofei Li; Changyi He; Siqing Lu (Process Safety and Environmental Protection, 2026)

Nano-SiO2-doped PVDF piezoelectric ultrafiltration membranes: Synergistic enhancement of antifouling performance via in situ microvibrations and hydrophilic optimization - Haijun Gao; Linjin Li; Guangfei Qu; Rui Xu; Junyan Li; Yingying Cai; Minghua Chen; Xinxin Liu; Xiaofei Li; Changyi He; Jiao Wei (Desalination, 2026)

Landfill leakage location based on an induced polarization method - Yayu Chen; Shibin Liu; Chaozhi Cai; Weimin Zhang; Hongzhuo Jin; Suxian Zhao; Junfeng Shen; Rui Wang (Environmental Monitoring and Assessment, 2026)

Experimental study on the wave mitigation characteristics of a grid-type flexible-membrane breakwater under regular waves - Chuan-Rui Li; Jing-Ping Wu; Ming-Liang Cai; Jun-Ao Kang; Chang-Zhe Chen; Hong Fan; Chen-Xia Liu; Shi-Yu Yang; Zi-Wen Xu (Ocean Engineering, 2026)

Erosion control performance of geomats on silty soil slopes under simulated rainfall - Rui Zhang; Xiwei Zhang; Kang Chen; Yipeng Guo; Yanhua Yu; Huanhua Cai (Geotextiles and Geomembranes, 2026)

NiCo layered double hydroxide nanosheet films for electrochromic supercapacitors - Haitao Li; Wenping Shi; Rui Fang; Chunyu Shi; Yang Liu; Yuli Xiong; Chunxia Zhao; Guofa Cai; Wen Chen (Chemical Engineering Journal, 2026)

Low abundance microorganisms enhance soil multifunctionality by emphasizing fungal roles as mediated by plant biomass - Ze-Ying Zhao; Xiao-Bin Xiong; Peng-Yang Wang; Jia-Cheng Guo; Yinglong Chen; Hong-Yan Tao; Nan Chang; Cheng-Rui Bi; Yun-Lu Chen; Yuan Song; You-Cai Xiong (Applied Soil Ecology, 2026)

CRISPR Epigenome Editing of IL1R1 Expression of Neurons that Innervate the Temporomandibular Joint or Knee Causes Reduced Sensitization to Osteoarthritic Environment - Joshua D. Stover; Robby D. Bowles; Yenisel Cruz-Almeida; Robert M. Caudle; Kyle D. Allen; Armen Akopian; Benjamin Arenkiel; Basak Ayaz; Yangjin Bae; Bruna Balbino de Paula; Anita Bandrowski; Mario Danilo Boada; et al. (Annals of Biomedical Engineering, 2026)

Gradient fluorination strategy to screen asymmetric ether for high-voltage and low-temperature lithium metal batteries - Junkai Shi; Rui Qiu; Zehang Peng; Ye Xiao; Liting Chen; Yuanzhu Zhong; Chao Xu; Yuepeng Cai; Fujun Li; Qifeng Zheng; Kui Ding (Science Bulletin, 2026)

Integrated metabolomics and transcriptomics analyses provide insights into flavor and color regulation during tomato postharvest ripening - Xian-Kang Xiao; Wei-Xin Liu; Xiao Lu; Cai-Rui Chen; Xin-Yi Zhang; Xiao-Jun Pu; Feng Wang (Postharvest Biology and Technology, 2026)

Gel-mediated hybrid co-coagulation enables effective removal of toxin-producing Cylindrospermopsis raciborskii: Interfacial energy restructuring and flocs morphology reshaping - Chen Huanghui; Ma Qianli; Yao Lingai; Zhao Rui; Gou Ting; Liang Rongchang; Feng Yanhui; Kang Hang; Gong Shihao; Yang Tiantian; Cai Qijia (Journal of Environmental Chemical Engineering, 2026)

Advances and challenges in multi‑scale water environment system modeling: from process simulation to a novel simulator architecture - Rui Xia; Sheng Chen; Yan Ding; Mingdong Sun; Yali Wu; Kaifang Shi; Yajing Cai; Kai Zhang; Yan Chen; Lei Zou (Ecological Modelling, 2026)

Microbiome differentiation and phenotypic variation of Pyropia haitanensis under two contrasting aquaculture environments - Fengjuan Li; Yi Liu; Qijun Luo; Juanjuan Chen; Rui Yang; Wenrong Zhu; Huifeng Cai; Haimin Chen (Aquaculture, 2026)

RSK2 facilitates beige fat formation through thermogenic and glycolytic pathways - Yan Cai; Jun-jun Chen; Lin-fei He; Yao Xu; Rui-qi Yang; Zhi-chun Yang (Journal of Thermal Biology, 2026)

Synergistic pathogenic mechanisms of EHP and IHHNV co-infection in Litopenaeus vannamei: Insights from RNA-seq analysis - Lin-Rui Chang; Cai-Yi Chen; Fan Yang; Chuan-Yu He; Fan Li; Ting Li; Ling-Jun Si; Dong-Chun Yan (Journal of Invertebrate Pathology, 2026)

Self-adaption ultra-small coordination polymer-incorporated nanofibers for multipronged management of diabetic wounds - Peirong Zhou; Min Jiang; Silei Li; Xuemin Ma; Yajuan Hu; Junliang Chen; Yun He; Gang Tao; Rui Cai (Chemical Engineering Journal, 2026)

Defect passivation with Pb for high-performance Sb2S3 solar cells via vapor transport deposition - Gan Huang; Xin-Yi Cai; Hu Li; Jin-Rui Cai; Ying-Sen Xia; Zhi-Ping Huang; Li-Mei Lin; Fu-Bao Gong; Shui-Yuan Chen; Gui-Lin Chen (Chemical Engineering Journal, 2026)

Simulated Microgravity affects immune reaction to infection through altering lymphocyte differentiation, cytokine secretion, and macrophage polarization - Hongyan Cai; Rui Jia; Huimin Chen; Yingying Wu; Yaya Qin; Shaoyan Si; Lei Zhu; Xiaotong Lou; Xiangru Li (Life Sciences in Space Research, 2026)

Sound velocities of Anorthite at high pressures and temperatures: Implications for estimating porosity in upper lunar crust - Peng Chen; Duojun Wang; Nao Cai; Rui Zhang; Junsheng Ma; Baocun Wang; Yinan Sun; Chunyin Zhou; Ke Yang (Icarus, 2026)

A metal-immuno photosensitizer strategy: Iridium(III)-zidovudine conjugate triggering sequential organelle stress and synergizing with PD-L1 inhibitor in oral squamous cell carcinoma - Yi-Ling Li; Peng Wang; Wu-Ya Zhang; Rui Zhou; Jia-Ying Zhou; Jia-Wen Chen; Jia-Yin Wu; Bin Cheng; Cai-Ping Tan; Tong Wu (Chemical Engineering Journal, 2026)

Salinity-driven trade-offs between nitrogen removal and microbiome dynamics in Fe-C-CWs toward saline aquaculture tailwater management - Xiaona Ma; Tangfang Zhai; Xuli Bao; Ziheng Wu; Yuxiang Yang; Rui Yin; Chen Cai; Gang Liu (Water Research, 2025)

Prenatal BPB/BPAF exposure induces depression-like behavior in male mice offspring via compound-specific transcriptional dysregulation and neurodevelopmental pathway alterations - Nannan Chen; Yuetong Liu; Yiran Zhouguo; Xueyi Cai; Xinyi Pan; Rui Guo; Wei Yan (NeuroToxicology, 2025)

Effects of representative Chinese cattle breeds on the eating quality and microstructure of braised beef - Jian Hu; Xiaoke Fu; Yijie Cai; Ronglan Wang; Rui Xu; Chengrong Zheng; Xing Chen; Bowen Yan (International Journal of Gastronomy and Food Science, 2025)

Efficient fabrication of micro/nanostructured porous film integrating excellent radiative cooling, robust water repellence and unidirectional moisture permeability by micro extrusion roll forming - Yunjia Cai; Yu Du; Yingying Chen; Rui Tong; Feicong Fan; Heng Xie; Ting Wu; Jinping Qu (Chemical Engineering Journal, 2025)

Point-of-care testing of neuromyelitis optica spectrum disorder using a sonochemically enhanced bifunctional CdTe-ZIF-8 nanohybrids-labelled lateral flow immunoassay - Qing Fu; Manxia Wang; Jia Shu; Guangjun Xiao; Zhujun Ai; Xin Gao; Huan Cai; Yan Zhao; Xuhuai Fu; Zhizhong Li; Mengjie Zhang; Jinzhou Feng; et al. (Chemical Engineering Journal, 2025)

A pH/ROS dual-responsive hydrogel promotes diabetic wound healing by controlled release of O2 and EGCG to induce angiogenesis and immunomodulation - Yongcen Chen; Xuemin Ma; Yajuan Hu; Huiyue Wang; Peirong Zhou; Xiaoping Tian; Haofeng Wang; Yun He; Gang Tao; Rui Cai; Junliang Chen (Chemical Engineering Journal, 2025)

pH/ROS responsive hydrogel loaded with bimetallic phenolic nanoparticles: A multifaceted therapeutic strategy for accelerating diabetic wound repair - Jing Zhou; Rui Shi; Chuankai Zhang; Yongcen Chen; Xuemin Ma; Yajuan Hu; Yun He; Gang Tao; Rui Cai (Chemical Engineering Journal, 2025)

Correction: Combining network Pharmacology and metabonomics to explore the mechanism of baicalin inhibiting PRRSV replication - Qin Luo; Yu-xuan Huang; Hai-rui Li; Chang-hong Qiao; Zhen-wen He; Xiang-yu Chen; Xiao-hu Wang; Gang Wang; Meng-meng Zhao; Ru-jian Cai (Veterinary Research Communications, 2025)

Combining network pharmacology and metabonomics to explore the mechanism of baicalin inhibiting PRRSV replication - Qin Luo; Yu-xuan Huang; Hai-rui Li; Chang-hong Qiao; Zhen-wen He; Xiang-yu Chen; Xiao-hu Wang; Gang Wang; Meng-meng Zhao; Ru-jian Cai (Veterinary Research Communications, 2025)

Metformin suppresses gammadelta T17 cell differentiation alleviating DSS-induced colitis - Mingzhong Sun; Hongli Liu; Huixiang Ju; Hongmei Chen; Rui Yang; Dongmei Yan; Langping Shen; Aiting Cai; Yaru Zhi; Lihua Xiao; Qinfang Tang; Yungang Wang (Immunologic Research, 2025)

Impact of thallium contamination on microbial communities and biogeochemical cycles in freshwater ecosystems - Shuang Yan; Yongxin Bing; Qianli Ma; Rui Zhao; Xiaodie Cai; Yuyin Yang; Sili Chen; Shuguang Xie (Aquatic Ecology, 2025)

Theasinensin A: Formation, preparation, and bioactivities of a promising functional polyphenol in tea - Yiang Chen; Juan Wang; Yuexin Liu; Fuqing Bai; Jiali Yang; Rui Shi; Huimei Cai; Zhongwen Xie; Daxiang Li; Yujie Huang; Guijie Chen (Trends in Food Science & Technology, 2025)

Morphology and nutrient content of bamboo rhizomes: Responses to enclosure succession in a Phyllostachys edulis forest in Wuyi Mountains, China - Xing Cai; Rui Cheng; Zhenhua Chen; Jiannan Lin; Min Wu; Jiaying Liu; Jihong Xiao; Yuchen Lin; Lingyan Chen; Yirong Zhang; Jundong Rong; Tianyou He; et al. (Forest Ecology and Management, 2025)

Mitochondria-targeted piezoelectric catalyst regulate pyroptosis and efferocytosis for enhancing the osteosarcoma immunogenic death - Linbang Wang; Rui Dou; Yunlong Ma; Jiayu Zhang; Xiaomeng Cai; Jinkun Liu; Xiaoguang Liu; Jun Chen (Chemical Engineering Journal, 2025)

A copper-based single-atom material effectively controls plant diseases with nearly zero soil residue and low phytotoxicity - Rui Huang; Yong Yan; Yafei Jiang; Chunyan Gu; Zhentao Ma; Lifang Xue; Yao Ma; Xingen Lin; Juan Zhang; Ran Shi; Yiwen Wang; Linjing Liu; et al. (Science Bulletin, 2025)

Bioinspired conductive-catalytic network accelerates rate-determining steps at cathode-electrolyte interface for high-loading Li-S batteries - Cai-Yun Zhang; Chen-Yang Wang; En-Zhu Zhao; Guowei Yu; Hui-Ling Deng; Rui Huang; Zhao-Yun Wang; Pu Hu; Min Yan; Zhitian Liu (Chemical Engineering Journal, 2025)

Rockburst Severity Prediction Under Few-Shot Conditions Using Feature Fusion Learning - Xin Cai; Liye Chen; Yichao Rui; Ruishan Cheng; Zilong Zhou; Jixiong Zhang; Hang Yuan; Yunmin Wang (Natural Resources Research, 2025)
Accurate and efficient prediction of rockburst severity is crucial for the safe construction of deep rock engineering, but only a limited number of recorded rockburst data cannot enable the reliable prediction. This paper presents an innovative method for predicting rockburst severity, termed Feature Fusion Learning (FFL). It combines feature fusion with machine learning models and category voting techniques, enabling square-level amplification of sample data to address the challenge of few-shot in predicting rockburst severity. The performance of this method is evaluated against two typical data augmentation techniques (i.e., noise injection and synthetic minority over-sampling technique) combined with three machine learning models (i.e., extreme gradient boosting, light gradient boosting machine, and random forest). The results indicate that the FFL method exhibits superior performance across all metrics compared to the other models. In addition, feature importance assessments and a comparative study on the effect of amount of prior data on the prediction performance of the FFL method are conducted. The results reveal that the FFL method effectively enriches the feature dimensions while preserving the information and properties of the original feature variables. Moreover, the FFL method shows high robustness when applied to datasets with varying sample sizes.

Targeted and non-targeted analyses reveal trophic biomagnification of rubber-derived chemicals in an estuarine food web near China's largest rubber production region - Yuan Liu; Jia-Ming Zhou; Nian-Nian Wu; Shan Liu; Xiao-Liang Liao; Haijiang Wu; Lin Zhu; Heng-Xiang Li; Lang Lin; Rui Hou; Zhi-Hua Li; Xiang-Rong Xu; et al. (Journal of Hazardous Materials, 2025)

Experiment-based optimization of rebar bond-slip behavior and damage evolution analysis of slab track - Zelin Chen; Xiaopei Cai; Jinhui Li; Yanglong Zhong; Rui Zhou (Engineering Structures, 2025)

An ultrasound-visualized methionine partitioning nano-modulator for enhanced immunotherapy against anti-PD-1 resistant tumors - Yingying Zhao; Beibei Zhang; Shaobo Duan; Yaqiong Li; Yuzhou Wang; Yongchao Wang; Juan Zhang; Rong Huang; Ru Jiang; Rui Zhang; Qi Zhou; Linlin Zhang; et al. (Chemical Engineering Journal, 2025)

Functional nucleic acid-stabilized selenium nanotechnology enable synergistic healing of diabetic chronic wounds - Si-Wei Yang; Jing Wang; Yan Tan; Xiao Jing; Chen-Yu Wang; Zhi-Li Yao; Wen-Hui Wang; Yong-Ji Li; Hao-Rui Li; Yan Zhao; De-Ming Kong; Qi-Liang Cai (Chemical Engineering Journal, 2025)

Identifying groundwater anthropogenic disturbances and their predominant impact on microbial nitrogen cycling at a former contamination site adjacent to Baiyangdian Lake - Sining Zhong; Bin Li; Qian Chen; Jinzheng zhang; Hetong Cai; Rui An; Guohong Liu; Shungui Zhou (Water Research, 2025)

Constructing asymmetric D′-A-D" imine covalent organic frameworks to optimize exciton effect and enhance photocatalytic reduction of U(VI) - Yang-Xing He; Xiao-Juan Chen; Rui Zhang; Hao-Xuan He; Cheng-Peng Niu; Cheng-Rong Zhang; Zhi-Hai Peng; Yuan-Jun Cai; Zhen-Wen Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2025)

Correlation study of 5-HT in brain with cognitive function and anxious-like behavior in APP/PS1 transgene mice - Li Yuan; Linshan An; Rui Xie; Jiahong Cai; Dong Li; Xiaorong Chen; Wenjing Guo; Yinran Lin; Chunjing Zhu; Yongli Chang; Kunbo Wang; Weina Han; et al. (Sleep and Biological Rhythms, 2025)

Human dental follicle cell-derived conditioned media enhance periodontal regeneration by regulating the osteogenic differentiation and inflammation of periodontal ligament stem cells and macrophage polarization - Yichen Gao; Xianyi He; Yuyao Deng; Xia Wang; Jie Shen; Wei Xu; Rui Cai; Xiaorong Lan; Junliang Chen; Yun He (Molecular and Cellular Biochemistry, 2025)

Cerebellar large-scale network connectivity in Parkinson’s disease: associations with emotion, cognition, and aging effects - Chentao He; Zhenzhen Chen; Mengfei Cai; Piao Zhang; Hao Li; Xi Chen; Qi Qi; Rui Yang; Yan Li; Zaiyi Liu; Lijuan Wang; Yuhu Zhang (Brain Imaging and Behavior, 2025)

Synthetic microbiome and biochar enhanced human feces aerobic mesophilic composting - Xiaoyu Cai; Jing Wang; Kun Feng; Huihui Zhou; Chuan Chen; Chuandong Wu; Rui Fang; Defeng Xing (Resources, Conservation and Recycling, 2025)

Experimental and consolidation modeling of flowing mud during vacuum preloading considering transient clogging and vacuum pressure attenuation - Yuefu Zhou; Rui Chen; Yuanqiang Cai; Jun Wang; Peng Wang; Dong Su; Xiangsheng Chen (Geotextiles and Geomembranes, 2025)

Ag nanowires boost graphene aerogel as anode for charge-transfer in nonclassical electroactive microbial fuel cells - Bo Yan; Yingzhu Guo; Shujian Cheng; Liangding Dou; Yun Yang; Xiaoxiao Guo; Yangbo Chen; Weiwei Cai; Yufeng Zhang; Zhe Liu; Zhaohui Meng; Rui Mu; et al. (Fuel, 2025)

Cation-induced phase transformation in PVDF for efficient energy harvesting - Dinku Hazarika; Jiaqi Lu; Jiafeng Ni; Chuanrui Chen; Muhammad Naeem Shah; Liangquan Xu; Jianhui Wu; Kaihang Zhang; Jie Li; Xinyu Cai; Rui Wan; Hao Jin; et al. (Chemical Engineering Journal, 2025)

Iron isotopic fractionation during seafloor hydrothermal alteration of oceanic upper crust, as recorded in Geotimes lavas of Semail ophiolite, Oman - Rong-Zhong Bo; Yildirim Dilek; Wei-Qiang Li; Sobhi Nasir; Peng-Jie Cai; Hui-Chao Rui; De-Hong Du; Shi-Chao An; Yu-Xiao Lu; Hao-Chen Duan; Dong-Yang Lian; Jing-Sui Yang; et al. (Chemical Geology, 2025)

CORBES: Radiation belt survey with international small satellite constellation - Ji Wu; Li Deng; Jaan Praks; Marius Anger; Philipp Oleynik; Wojciech Hajdas; Jin-Dong Wang; Shen-Yi Zhang; Bin Zhou; Li Zeng; Jinbin Cao; David Fischer; et al. (Advances in Space Research, 2025)

Sand Production and Critical Rate in Stress-Sensitive Unconsolidated Sandstone: An Experimental Study - Xiao-Hua Tan; Rui Wang; Xiao-Jun Zhou; Yao Zhu; Cai-Shen Li; Bo Cao; Zhi Yang; Hao Chen; Bao-Quan Wen; Liu Tang; Huan-Yu Ran (Geotechnical and Geological Engineering, 2025)

Combined uranium-series and trace elements analysis in cold seep bivalves: possibility in hundred-year-scale reconstruction of deep-sea temperature and acidification - Chaofeng Cai; Jing-Chun Feng; Guozhong Wu; Rui Hou; Xiao Chen; Jinyi Liu; Xiaochun Zhang; Si Zhang (Frontiers in Marine Science, 2025)
Despite the pivotal role of deep-sea in the global climate system, effective technology is still limited for reconstructing the key parameters of deep-sea environment such as temperature and acidification, especially at the hundred-year scale. In this study, we assessed the robustness and reliability of using bivalve shells in reconstructing cold seep environments. A significant heterogeneous distribution of trace elements was observed in the shells of clams and mussels from Formosa and Haima cold seeps even if they were collected from the same site, which was caused mainly by the environmental variables rather than physiological characters. The results of the principal component analysis revealed different trace elements ratios in the shell were associated with seepage. In particular, Sr/Ca was identified as a reliable proxy for temperature reconstruction, which performed better than oxygen isotopes. Na/Ca and U/Ca are potential proxies for cold seep acidification, but further validation is needed before their practical application. The age bias using the U-series dating method resulted from high 232 Th and low initial 230 Th/ 232 Th rather than from alpha-recoil processes. The median ages assigned to mussels from the F and Haima cold seeps were 229.5 and 323.5 years, respectively. The lifespan of clams from the Haima cold seep was too short to date accurately. We proposed to conduct feasibility verification and error correction to enhance the method performance in reconstructing the hundred-year evolution of cold seep environment in the South China Sea.

Environmental factors ultraviolet a and ozone exacerbate the repeated inhalation toxicity of 6PPD in mice via accelerating the aging reaction - Xianjie Li; Caixia Wu; Ping Yang; Yanxi Li; Shuai Wang; Dan Cai; Ran Wei; Jinfeng Gao; Xuemei Wen; Jieping Luo; Rui Wang; Xueyuan Bai; et al. (Journal of Hazardous Materials, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Sericin-based conductive hydrogel loaded with MXene@TA-Eu nanosheets promotes the healing of infected wounds through photothermal antibacterial and electrical stimulation - Chuankai Zhang; Peirong Zhou; Yuyao Deng; Xuemin Ma; Yajuan Hu; Yongcen Chen; Xia Wang; Gang Tao; Yun He; Rui Cai; Junliang Chen (Chemical Engineering Journal, 2025)

Efficient sustainable production of protocatechuic acid from glucose by engineered Bacillus licheniformis - Yi Rao; Jiaqi Wang; Rui Zhao; Yangyang Zhan; Xin Ma; Penghui He; Dongbo Cai; Shouwen Chen (Chemical Engineering Journal, 2025)

Co-doped 1T-MoS2 adsorbent: Efficient removal of Hg0 from flue gas - Qian Cai; Ping He; Jiang Wu; Naichao Chen; Rui Shen; Kangsai He; Tianyang Hu; Litao Zhang; Wenchu Yuan; Xingyu Cao (Chemical Engineering Journal, 2025)

Strengthening H2 gas–liquid mass transfer using superaerophobic cathodes for enhanced methane production from CO2 in H2-mediated microbial electrosynthesis system - Jia-Yao Gao; Wen-Fang Cai; Ji-Rui Bai; Yu-Cheng Zhu; Yu-Xiao Zhang; Sheng Wang; Kun Guo; Qing-Yun Chen; Yun-Hai Wang (Bioresource Technology, 2025)

Factors governing bark tufa deposition in fluvial systems: the case study of Nuorilang in Jiuzhaigou, Sichuan China - JunHao Li; FuDong Wang; WuYang He; QinYingZi Cai; Shi Chen; GuoQing Huang; Dawood Muhammad; Carlos Pérez-Mejías; Rui Zhang; ZiTong Peng; SiRui Chen; ChenWei Ji; et al. (Carbonates and Evaporites, 2025)

Microglia programmed cell death in neurodegenerative diseases and CNS injury - Ling Cai; Qiuyue Fan; Rui Pang; Chen Chen; Yueman Zhang; Haiyi Xie; Jingyi Huang; Yu Wang; Peiying Li; Dan Huang; Xia Jin; Yuxi Zhou; et al. (Apoptosis, 2025)

Spatiotemporal estimates and health risks of atmospheric trace metals across Hong Kong during 2016–2020 - Wenwen Sun; Shenghua Zhang; Dongmei Cai; Liqiang Wang; Ji Jin; Rui Li; Zhenghu Chen (Air Quality, Atmosphere & Health, 2025)

Experimental investigation of natural gas leakage and dispersion characteristics in utility tunnels under the effects of real facility layout and forced ventilation - Jitao Cai; Jiansong Wu; Yuhang Wang; Chen Fan; Rui Zhou (Tunnelling and Underground Space Technology, 2025)

The source and differential enrichment mechanisms of lithium in Gudui geothermal field: Constraints from enrichment and dilution processes of geothermal-type lithium - Rui Cao; Yiming Yan; Ji Dor; Qijun Liu; Yongqiang Cai; Shuangshuang Wan; Defan Chen (Geothermics, 2025)

Distribution and genesis of geothermal waters in the Xianshuihe fault zone, Western Sichuan plateau, China: Constraints on fracture system and regional seismic activities - Rui Cao; Yongqiang Cai; Ji Dor; Qijun Liu; Mariia Poliakova; Defan Chen; Shuangshuang Wan; Yiming Yan (Geothermics, 2025)

Reduced phytoplankton biomass in a subtropical plume-upwelling system induced by typhoons Bailu and Podul - Zhuyin Tong; Lingqi Ma; Shujie Cai; Zhaoyun Chen; Lei Wang; Mingwang Xiang; Rui Huang; Meilin Wu; Wupeng Xiao; Bangqin Huang (Progress in Oceanography, 2024)

Specialized metabolites of the endophyte Annulohypoxylon areolatum hosted by Aconitum carmichaelii - Cheng-Yao Wang; Dong Gan; Yan Shu; Rui-Feng Mei; Jia-Qi Liu; Chen-Zhe Li; Lan Cai; Sheng-Qi Zhang; Li Zhu; Hao Zhou; Le Cai; Zhong-Tao Ding (Phytochemistry, 2024)

Phosvitin phosphopeptides and peptides-calcium chelate promote calcium deposition in a three-cell co-culture system by modulating the OPG/RANKL/RANK signaling pathway - Jiaojiao Chen; Songming Li; Mahmoud Abou-Elsoud; Wei Liu; Rui Cui; Zuyue Li; Dewei Shu; Zhaoxia Cai; Xi Huang (Food Bioscience, 2024)

Assessing soil remediation effect of Cr and Pb based on bioavailability using DGT, BCR and standardized determination method - Rui Chen; Jingyan Yang; Xuying Cai; Zean Liu; Wenyang Huang; Rongguang Shi; Tiantian Ma (Science of The Total Environment, 2024)

Preparation and properties of cationic starch-carrageenan‑sodium alginate hydrogels with pH and temperature sensitivity - Zheng Cai; Wei Zhou; Wenjing Chen; Rui Huang; Rui Zhang; Li Sheng; Miaomiao Shi; Yong Hu; Chao Huang; Yun Chen (Food Chemistry, 2024)

Nitrogen reduction enhances crop productivity, decreases soil nitrogen loss and optimize its balance in wheat-maize cropping area of the Loess Plateau, China - Jinjin Wang; Rui Qian; Jiaxiang Li; Funan Wei; Zhimeng Ma; Sisi Gao; Xu Sun; Peng Zhang; Tie Cai; Xining Zhao; Xiaoli Chen; Xiaolong Ren (European Journal of Agronomy, 2024)

Tuning local charge polarization of covalent organic frameworks for enhanced photocatalytic uranium (VI) reduction - Xiao-Xing Wang; Cheng-Rong Zhang; Rui-Xiang Bi; Zhi-Hai Peng; Hao-Xuan He; Rui Zhang; An-Min Song; Jia-Xin Qi; Xiao-Juan Chen; Xin Liu; Yuan-Jun Cai; Ru-Ping Liang; et al. (Chemical Engineering Journal, 2024)

Residual plastic film decreases crop yield and water use efficiency through direct negative effects on soil physicochemical properties and root growth - Xiaobo Gu; Rui Yin; Wenjing Cai; Pengpeng Chen; Kui Cui; Yadan Du; Yuannong Li; Huanjie Cai (Science of The Total Environment, 2024)

Fabrication and characterization of oxidized starch-xanthan gum composite nanoparticles with efficient emulsifying properties - Zheng Cai; Wei Zhou; Rui Zhang; Yuqi Tang; Kun Hu; Fangfang Wu; Chao Huang; Yong Hu; Tao Yang; Yun Chen (Food Chemistry, 2024)

Salinity-induced variations in bacterial composition and co-occurrence patterns within Salicornia-based constructed wetlands in mariculture - Xiaona Ma; Tangfang Zhai; Xinyuan Wang; Chen Cai; Denggao Qiu; Rui Yin; Jiayu Li; Gang Liu (Chemosphere, 2024)

Liquidizing crystal MIL-100(Fe) to coating silica powder for purifying wastewater - Shiyong Wei; Aijia Cao; Siyuan Huang; Yao Shen; Ting Lei; Songmei Luo; Mingjun Cai; Wenjun Xiang; Anying Chen; Rui Wang (Chemical Engineering Journal, 2024)

Cyclic tensile stress promotes osteogenic differentiation via upregulation of Piezo1 in human dental follicle stem cells - Binqing Xie; Xianyi He; Ye Guo; Jie Shen; Binbin Yang; Rui Cai; Junliang Chen; Yun He (Human Cell, 2024)

MARCH1 and MARCH2 inhibit pseudorabies virus replication by trapping the viral cell-to-cell fusion complex in trans-Golgi network - Rui Huang; Cui-Hong Rao; Yuan-Zhe Bai; Changqing Yu; Meng Chen; Jin-Mei Peng; Shi-Jia Xu; Yue Sun; Meng Fandan; Chuang Lyu; Mirwaise Khan; Tong-Qing An; et al. (Veterinary Microbiology, 2024)

Karst carbon sink mechanism and its contribution to carbon neutralization under land- use management - Min Zhao; Dong Li; Zaihua Liu; Qian Bao; Fan Xia; Hao Yan; Bo Chen; Yundi Hu; Guanxia Cai; Rui Lang; Hang Li; Liangxing Shi; et al. (Science of The Total Environment, 2024)

Synthesis of a graphene oxide-based zerovalent iron nanocomposite for efficient remediation of Re(VII) from simulated wastewater in high pH - Yixin Pan; Yanbin Cai; Lujia Chen; Leilei Sun; Liping Deng; Rui Huang (Journal of Water Process Engineering, 2024)

Astaxanthin Rescues Memory Impairments in Rats with Vascular Dementia by Protecting Against Neuronal Death in the Hippocampus - Na Wei; Luo-man Zhang; Jing-Jing Xu; Sheng-lei Li; Rui Xue; Sheng-li Ma; Cai Li; Miao-miao Sun; Kui-sheng Chen (NeuroMolecular Medicine, 2024)

Effect of annealing treatment on physicochemical properties, rheology and in vitro digestion of potato starch-galactomannan complexes - Rui Zhang; Rui Huang; Zheng Cai; Yuqi Tang; Yong Hu; Chao Huang; Nanjing Zhong; Yun Chen (Food Hydrocolloids, 2024)

Sustainable reprocessing of lithium iron phosphate batteries: A recovery approach using liquid-phase method at reduced temperature - Tingyan Ren; Bolin Zou; Bin Cai; Tong Liang; Junhao Chen; Rui Huang; Dahai Yang; Hongfa Xiang; Edison Huixiang Ang; Xiaohui Song (Waste Management, 2024)

Celastrol induced the autophagy of spermatogonia cells contributed to tripterygium glycosides-related testicular injury - Dong-Xiao Cui; Ze-Chen Niu; Xi Tang; Chun-Zhou Cai; Ding-Qiao Xu; Rui-Jia Fu; Wen-Juan Liu; Yu-Wei Wang; Yu-Ping Tang (Reproductive Toxicology, 2024)

Enteral nutrition in the management of acute pancreatitis: Modulates gut microbiome and alleviates inflammation - Fang-Yuan Yang; Yi-Jing Cai; Xiao-Ying Niu; Shun-Fu Wang; Yu-Qi Wang; Sabola Eluby Esmie; Rui-Cong Chen; Sheng-Jie Dai; Hong-Ru Kong; Hong-Wei Sun; Ke-Qing Shi (Food Bioscience, 2024)

Cadmium interacts with nitrogen level and nitrogen form to affect the growth of an invasive plant Alternanthera philoxeroides - Dan Li; Xiao-Gai Wang; Jia-Xin Yang; Yu-Fei Hu; Wen-Yue Lyu; Jun-Cai Xin; Rui Zhang; Zhi-Huan Chen; Chao Si (Aquatic Ecology, 2024)

Application of a biofilm-enhanced A2O system in the treatment of wastewater from mariculture - Xiaona Ma; Rui Yin; Chen Yang; Chen Cai; Jufan Zhao; Chuxiu Lv; Xinchen Wang; Shiyu Chen; Jilong Ren; Bingzhi Zhang (Frontiers in Marine Science, 2024)
Development of environment-friendly and efficient aquaculture effluent treatment system is crucial for sustainable intensification of aquaculture, in the face of the rapidly increasing environmental pressure in the mariculture industry. In this study, mariculture wastewater was treated by the anoxic-anaerobic-oxic biochemical treatment system (A 2 O system) with traditional activated sludge replaced by nitrifying bacteria, denitrification bacteria and phosphorus accumulating bacteria absorbed on PBS carrier biofilms suitable for saline/brackish water. The results showed that biofilm-enhanced A 2 O system can effectively remove pollutants from aquaculture wastewater. The removal efficiencies of COD Mn , NH 4 + -N, TN and TP in A 2 O system were approximately 86.3%-90.8%, 97.7%-99.5%, 94.6%-95.2% and 97.0%-98.1%. The results further showed that COD Mn , NH 4 + -N, and TN were mainly removed in anaerobic tank and anoxic tank, while TP was mainly removed in the anoxic tank and oxic tank. The biofilm-enhanced A 2 O system by adding nitrifying bacteria and phosphorus accumulating bacteria biofilms using PBS as carriers instead of conventional activated sludge could be applied to the treatment of circulating aquaculture wastewater. This study provides a feasible scheme for enhancing the efficiency of A 2 O system in the treatment of aquaculture tail water, and provides a reference for the immobilization of microorganisms.

Hypoxia inducible factor-1α facilitates transmissible gastroenteritis virus replication by inhibiting type I and type III interferon production - Yunhang Zhang; Xue Rui; Yang Li; Yue Zhang; Yifei Cai; Chen Tan; Ning Yang; Yuanyuan Liu; Yuguang Fu; Guangliang Liu (Veterinary Microbiology, 2024)

Uncovering the coupling effect with energy-related carbon emissions and human development variety in Chinese provinces - Liu Chen; Yiqi Tan; Gengpei Lv; Weiguang Cai; Xiaofeng Gao; Rui Li (Journal of Environmental Sciences, 2024)

Self-enhanced nanohydrogel electrochemiluminescence biosensor based on CRISPR/Cas12a and gold platinum nanoparticles modification for high-sensitivity detection of Burkholderia pseudomallei - Yuexin Wang; Bo Shen; Nini Luo; Cai Li; Haiping Wu; Yanshuang Wang; Shen Tian; Xuemiao Li; Rui Liu; Xinmin Li; Junman Chen; Wei Cheng; et al. (Chemical Engineering Journal, 2024)

Sound velocities of Tremolite at high pressure: Implications for detecting water on Venus - Peng Chen; Duojun Wang; Nao Cai; Kenan Han; Jikai Zhang; Rui Zhang; Yang Cao (Icarus, 2024)

Preparation and properties of pH-sensitive cationic starch nanoparticles - Wei Zhou; Rui Zhang; Zhen Cai; Fangfang Wu; Yong Hu; Chao Huang; Kun Hu; Yun Chen (Food Chemistry, 2024)

Equilibrating provincial carbon increments for residential buildings in China under carbon peaking constraints - Liu Chen; Rui Li; Jinbo Zhang; Weiguang Cai; Kaiqiang Zhang; Yida Sun (Environmental Impact Assessment Review, 2024)

Thermo-Hydro-Mechanic-Chemical coupling model for hydrate-bearing sediment within a unified granular thermodynamic theory - Rui Zhou; Bing Bai; Guoqing Cai; Xingxin Chen (Computers and Geotechnics, 2024)

The immune response of Caspase-3 gene in infectious hypodermal and hematopoietic necrosis virus (IHHNV) infection of Litopenaeus vannamei - Cai-Yi Chen; Ning Yang; Chuanyu He; Yang Gao; Lin-Rui Chang; Ting Li; Ling-Jun Si; Dong-Chun Yan (Aquaculture, 2024)

Inactivation of pathogenic microorganisms in water by electron beam excitation multi-wavelength ultraviolet irradiation: Efficiency, influence factors and mechanism - Yong-Qiang Li; Rui Sun; Chong-Miao Zhang; Zi-Xuan Liu; Rui-tao Chen; Jian Zhao; Hua-dong Gu; Huan-Cai Yin (Journal of Environmental Management, 2024)

AM fungus promotes wheat grain filling via improving rhizospheric water & nutrient availability under drought and low density - Hai-Xia Duan; Chong-Liang Luo; Rui Zhou; Ling Zhao; Shuang-Guo Zhu; Yinglong Chen; Ying Zhu; You-Cai Xiong (Applied Soil Ecology, 2024)

Effects of nutrients and light in aquatic habitat on the growth of Hydrocotyle vulgaris when expanded from terrestrial to aquatic habitat - Zhi-Huan Chen; Rui Zhang; Jun-Cai Xin; Zi-Han Qian; Shu-Jie Wang; Shang-Yan Qiu; Xue-Ge He; Chao Si (Aquatic Botany, 2024)

Historical peak situation of building carbon emissions in different climate regions in China: Causes of differences and peak challenges - Rui Li; Liu Chen; Weiguang Cai; Kairui You; Zhaoji Li; Lina Ran (Science of The Total Environment, 2023)

Spatial bandgap tailoring via a novel injection chemical bath deposition enables highly efficient carbon-based Sb2(S,Se)3 thin film solar cells - Peng Tang; Zi-Heng Huang; You-Xian Chen; Hu Li; Li-Quan Yao; Hui Li; Li-Mei Lin; Jin-Rui Cai; Ya-Lu Zhan; Dong Wei; Shui-Yuan Chen; Da-Qin Chen; et al. (Chemical Engineering Journal, 2023)

Mitochondrial dysfunction: a new molecular mechanism of intervertebral disc degeneration - Chao Song; Yulin Xu; Qinghua Peng; Rui Chen; Daqian Zhou; Kang Cheng; Weiye Cai; Tao Liu; Chenyi Huang; Zhijiang Fu; Cong Wei; Zongchao Liu (Inflammation Research, 2023)

Shear wave velocity structure of the upper crust in north Xiaojiang fault zone in SE Tibet via short-period ambient noise dense seismic array - Si Chen; Rui Gao; Zhanwu Lu; Yao Liang; Wei Cai; Lifu Cao; Zilong Chen; Guangwen Wang (Physics of the Earth and Planetary Interiors, 2023)

Development of a duplex PCR for the simultaneous detection of EHP and IHHNV and analysis of the correlation between these two pathogens - Yang Gao; Cai-Yi Chen; Zheng Cao; Ru-Qing Yuan; Lin-Rui Chang; Ting Li; Ling-Jun Si; Dong-Chun Yan; Fan Li (Journal of Invertebrate Pathology, 2023)

Surface engineered long-lasting antibacterial Janus cotton fabrics with excellent moisture/thermal management properties - Lujie Wang; Maoshuang Chen; Rui Cai; Jingjing Jiang; Shuangfei Xiang; Xiangdong Liu; Hongyan Diao (Chemical Engineering Journal, 2023)

Induction of Anxiety-Like Phenotypes by Knockdown of Cannabinoid Type-1 Receptors in the Amygdala of Marmosets - Lin Zhu; Di Zheng; Rui Li; Chen-Jie Shen; Ruolan Cai; Chenfei Lyu; Binliang Tang; Hao Sun; Xiaohui Wang; Yu Ding; Bin Xu; Guoqiang Jia; et al. (Neuroscience Bulletin, 2023)

Elastic properties of amphibole at high pressure: A new explanation of the low velocities anomaly in the mantle wedges - Jikai Zhang; Duojun Wang; Nao Cai; Rui Zhang; Peng Chen (Tectonophysics, 2023)

The sound velocity of garnet at high pressure: Implications for high velocity anomalies in cold subducting slabs - Peng Chen; Duojun Wang; Nao Cai; Jikai Zhang; Rui Zhang; Ruixin Zhang; Kenan Han; Yang Cao (Tectonophysics, 2023)

Bimodal interferences of Pb(II) induced by parallel deposition in Pb(II)-Cu(II) electrochemical detections: Voltammetric signals analysis combined with numerical simulations on transient interfacial phenomena - Rui-Ze Xia; Xin Cai; Bo Liang; Hai-Hua Dai; Yang-Zhi Liu; Meng Yang; Shi-Hua Chen; Pei-Hua Li; Xing-Jiu Huang (Journal of Hazardous Materials, 2023)

Rethinking personal carbon trading (PCT) mechanism: A comprehensive review - Yun-En Tang; Ru Fan; Ang-Zu Cai; Le-Yi Wang; Rui-Min Lin; Xiang-Zhou Meng; Ling Chen; Ru Guo (Journal of Environmental Management, 2023)

Citrus medica var. Sarcodactylus (Siebold ex Hoola van Nooten) Swingle: an insight into its botany, traditional uses, phytochemistry, and pharmacological properties - Qin-Ge Ma; Jie Chen; Li-Hua Chen; Guang Wu; Mei-Ning Zhu; Neng-Xin He; Qin-Yuan Wang; Zhi-Pei Sang; Cai-Qing Zhu; Yong-Zhong Wu; Rong-Rui Wei (Phytochemistry Reviews, 2023)

Revealing the solid-solution interface interference behaviors between Cu2+ and As(III) via partial peak area analysis of simulations and experiments - Bo Liang; Xiang-Yu Xiao; Zong-Yin Song; Yong-Yu Li; Xin Cai; Rui-Ze Xia; Shi-Hua Chen; Meng Yang; Pei-Hua Li; Chu-Hong Lin; Xing-Jiu Huang (Analytica Chimica Acta, 2023)

Collaborative removal of fine catalysts particles and insoluble organics from methanol-to-olefins reaction wastewater using horizontal swirl regeneration micro-channel separation (HSRMS) - Jianqi Chen; Rui Cai; Haitao Huang; Qi Wei; Bing Liu; Aosong Wei; Meng Zhang; Wenjie Lv; Hualin Wang (Process Safety and Environmental Protection, 2023)

Preparation and emulsification properties of cationic starch-xanthan gum composite nanoparticles - Wei Zhou; Zhen Cai; Rui Zhang; Kun Hu; Fangfang Wu; Yong Hu; Chao Huang; Yun Chen (Food Chemistry, 2023)

Identification and application of species-specific peptide biomarkers from soft-shelled turtles (Pelodiscus sinensis) using post-translational modification detection-based peptidomics analysis - Haoran Xia; Xun Liu; Shuo Cai; Shengjun Chen; Song Li; Ming Zhao; Jin-ao Duan; Rui Liu; Shuying Han (Food Chemistry, 2023)

Integrated design of aerodynamic and anti-flutter performance of offshore wind turbine airfoil based on full information cooperative game method - Rui Meng; Liangliang Chen; Ruxin Zhao; Xin Cai; Nenggang Xie (Ocean Engineering, 2023)

Study of infectious hypodermal and hematopoietic necrosis virus (IHHNV) infection in different organs of Penaeus vannamei - Zi-Hao Hou; Yang Gao; Jing-Jing Wang; Cai-Yi Chen; Lin-Rui Chang; Ting Li; Ling-Jun Si; Fan Li; Dong-Chun Yan (Journal of Invertebrate Pathology, 2023)

High-throughput calculation of organ-scale traits with reconstructed accurate 3D canopy structures using a UAV RGB camera with an advanced cross-circling oblique route - Shunfu Xiao; Yulu Ye; Shuaipeng Fei; Haochong Chen; Bingyu zhang; Qing li; Zhibo Cai; Yingpu Che; Qing Wang; AbuZar Ghafoor; Kaiyi Bi; Ke Shao; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Characterizations of food-derived ellagic acid-Undaria pinnatifida polysaccharides solid dispersion and its benefits on solubility, dispersity and biotransformation of ellagic acid - Zhao-Rong Li; Rui-Bo Jia; Xueyuan Cai; Donghui Luo; Chong Chen; Mouming Zhao (Food Chemistry, 2023)

Insight into mitochondrial dysfunction mediated by clozapine-induced inhibition of PGRMC1 in PC12 cells - Liwei Wang; Qian Chen; Rui Ma; Bikui Zhang; Ping Yang; Ting Cao; Shimeng Jiao; Hui Chen; Chenquan Lin; Hualin Cai (Toxicology, 2023)

Highly synergistic and polarized KNbO3/WO3 heterojunction for piezo-photocatalytic degradation of organic pollutant - Rui Huang; Wei Cai; Heng Zhang; Zhenhua Wang; Qin Zhang; Rongli Gao; Gang Chen; Xiaoling Deng; Xiang Lei; Jiling Dong; Xiaoyan Liu; Chunlin Fu (Journal of Environmental Chemical Engineering, 2023)

Dose-response and type-dependent effects of antiviral drugs in anaerobic digestion of waste-activated sludge for biogas production - Rui Wang; Wan Yang; Chen Cai; Menghuan Zhong; Xiaohu Dai (Environmental Science and Pollution Research, 2023)

Abundance and characteristics of microplastics in the Wanquan River estuary, Hainan Island - Tuan-Tuan Wang; Wang-Qing Tang; Dong-Hai Wu; Xin-Rui Yu; Guang-Yu Wang; Xing-Wei Cai; Shuai Shao; Sai Wang; Ling Mo; You-Sheng Liu; Guang-Guo Ying; Zhong-Bing Chen (Marine Pollution Bulletin, 2023)

Insights into the impact of quaternary ammonium disinfectant on sewage sludge anaerobic digestion: Dose-response, performance variation, and potential mechanisms - Wan Yang; Chen Cai; Rui Wang; Xiaohu Dai (Journal of Hazardous Materials, 2023)

Channeling analysis of wavelet threshold processing based on K-means clustering algorithm - Lixiong Gan; Ming Li; Wenyuan Cai; Jian Li; Zhanglong Chen; Jian Sun; Rui Deng (Acta Geophysica, 2023)

Bicarbonate enhanced heterogeneous activation of peroxymonosulfate by copper ferrite nanoparticles for the efficient degradation of refractory organic contaminants in water - Chun Cai; Yangfan Liu; Rui Xu; Jiaheng Zhou; Jin Zhang; Yu Chen; Lingyu Liu; Lexiang Zhang; Shuping Kang; Xianjun Xie (Chemosphere, 2023)

Ambient air pollution, bone mineral density and osteoporosis: Results from a national population-based cohort study - Yin Yang; Rui Li; Miao Cai; Xiaojie Wang; Haopeng Li; Yinglin Wu; Lan Chen; Hongtao Zou; Zilong Zhang; Haitao Li; Hualiang Lin (Chemosphere, 2023)

A novel model to predict the pyrolysis process with preciseness and conciseness: Complementation-Distributed Activation Energy Model (C-DAEM) - Rui Chen; Jun Cai; Xiaofang Wang; Weijian Song; Xinli Li; Qinggang Lyu (Fuel, 2023)

Interactive Effects of Maize Straw-Derived Biochar and N Fertilization on Soil Bulk Density and Porosity, Maize Productivity and Nitrogen Use Efficiency in Arid Areas - Ru Guo; Rui Qian; Ling Yang; Abdul Khaliq; Fei Han; Sadam Hussain; Peng Zhang; Tie Cai; Zhikuan Jia; Xiaoli Chen; Xiaolong Ren (Journal of Soil Science and Plant Nutrition, 2022)

Effects of rainfall and rocky desertification on soil erosion in karst area of Southwest China - Li-dong Pan; Rui Li; Dong-cai Shu; Li-na Zhao; Mei Chen; Jun Jing (Journal of Mountain Science, 2022)

Proteomic analysis of coarse and fine skin tissues of Liaoning cashmere goat - Zhixian Bai; Yanan Xu; Ming Gu; Weidong Cai; Yu Zhang; Yuting Qin; Rui Chen; Yinggang Sun; Yanzhi Wu; Zeying Wang (Functional & Integrative Genomics, 2022)

Screening and Characterization of Potential Antioxidant Probiotics Isolated from the Gut of Hybrid Grouper (Epinephelus fuscoguttatus ♀ × Epinephelus lanceolatus ♂) - Qian Zhang; Yan Cai; Zihan Chen; Huizhong Shi; Yongcan Zhou; Yang Yang; Rui Tu; Guisen Chen; Shifeng Wang (Frontiers in Marine Science, 2022)
Some symbiotic probiotics have antioxidant activities and could improve the antioxidant capacity of the host. There is still no report on the screening of host-derived antioxidant probiotics for grouper farming. In this study, 369 out of 583 isolates were screened from the gut of hybrid grouper ( Epinephelus fuscoguttatus ♀ × Epinephelus lanceolatus ♂ ) based on their non-hemolytic characteristics. Subsequent preliminary screening with 2,2-Diphenyl-1-Picrylhydrazyl (DPPH) scavenging rate assay resulted in 36 potential antioxidant isolates. After comprehensive evaluation with nine different antioxidant assays (DPPH scavenging rate, 2,2’-azino-bis (3-ethylbezothiazoline)-6-sulfonic acid radical scavenging rate, iron ion reducing ability, reducing activity, O 2 - · scavenging rate,·OH scavenging rate, ferrous ion chelating rate, hydrogen peroxide tolerance, oxygen-free radical scavenging ability, et al.), 10 isolates with strong antioxidant abilities were screened from 36 potential antioxidant isolates. Then some other probiotic properties, such as simulated gastrointestinal fluid tolerance, adhesion, digestive enzyme activity, and antibacterial activity of the 10 selected isolates were evaluated. All 10 isolates were also identified using the molecular method. Finally, Vibrio rhodolitus GO 91 and Shewanella corallii GO 310, as representatives of the two genera resulting from the identification of the 10 isolates, and with the best overall probiotic properties, were selected from the 10 isolates. Isolates GO 91 and GO 310 were further tested for their safety performances. Antibiotic sensitivity tests showed that GO91 and GO310 were sensitive to many commonly used aquaculture antibiotics. The in vivo challenge test of GO 91 and GO 310 didn’t cause any disease symptoms or death in hybrid grouper. Therefore, isolates GO 91 and GO 310 showed great potential to be used as probiotics in hybrid grouper farming.

Two new cytotoxic cycloartane triterpenoids from Aphanamixis polystachya (Wall.) R. N. Parker - Yi-ting Wang; Shi-rui Fan; Jie-yun Cai; Jing-jing Guo; Xin-fang Zhang; Bi-juan Yang; Xiao-jiang Hao; Duo-zhi Chen (Natural Product Research, 2022)

miRNA-Based Drought Regulation in the Important Medicinal Plant Dendrobium huoshanense - Yujuan Wang; Jun Dai; Rui Chen; Cheng Song; Peipei Wei; Yongping Cai; Yulong Wang; Bangxing Han (Journal of Plant Growth Regulation, 2022)

Function-specific projections from V2 to V4 in macaques - Chen Fang; Kun Yan; Chen Liang; Jiayu Wang; Xingya Cai; Rui Zhang; Haidong D. Lu (Brain Structure and Function, 2022)

Bmi1 Regulates Wnt Signaling in Hematopoietic Stem and Progenitor Cells - Hao Yu; Rui Gao; Sisi Chen; Xicheng Liu; Qiang Wang; Wenjie Cai; Sasidhar Vemula; Aidan C. Fahey; Danielle Henley; Michihiro Kobayashi; Stephen Z. Liu; Zhijian Qian; et al. (Stem Cell Reviews and Reports, 2021)

Ecological risk assessment of heavy metals in farmland soils in Beijing by three improved risk assessment methods - Rui Chen; Xuying Cai; Guoyu Ding; Fumin Ren; Qi Wang; Nuo Cheng; Jiaxing Liu; Lanxin Li; Rongguang Shi (Environmental Science and Pollution Research, 2021)

Long noncoding RNA-based drought regulation in the important medicinal plant Dendrobium huoshanense - Yujuan Wang; Jun Dai; Rui Chen; Cheng Song; Peipei Wei; Yulong Wang; Yongping Cai; Bangxing Han (Acta Physiologiae Plantarum, 2021)

The correlation of altitude with gingival status among adolescents in western China: a cross-sectional study - Zhiwu Wu; Rui Zhang; Li Cheng; Ruilie Cai; Hong Chen; Ran Cheng; Tao Hu (Environmental Geochemistry and Health, 2021)

Damage Evolution and Deformation of Rock Salt Under Creep-Fatigue Loading - Kai Zhao; Hongling Ma; Chunhe Yang; Xiangsheng Chen; Yibiao Liu; Xiaopeng Liang; Rui Cai (Rock Mechanics and Rock Engineering, 2021)

T4 ‐like myovirus community shaped by dispersal and deterministic processes in the South China Sea - Huifang Li; Lu Liu; Yu Wang; Lanlan Cai; Maoqiu He; Long Wang; Chen Hu; Nianzhi Jiao; Rui Zhang (Environmental Microbiology, 2021)
Summary As the most abundant and genetically diverse biological entities, viruses significantly influence ecological, biogeographical and evolutionary processes in the ocean. However, the biogeography of marine viruses and the drivers shaping viral community are unclear. Here, the biogeographic patterns of T4‐like viruses and the relative impacts of deterministic (environmental selection) and dispersal (spatial distance) processes were investigated in the northern South China Sea. The dominant viral operational taxonomic units were affiliated with previously defined Marine, Estuary, Lake and Paddy Groups. A clear viral biogeographic pattern was observed along the environmental gradient from the estuary to open sea. Marine Groups I and IV had a wide geographical distribution, whereas Marine Groups II, III and V were abundant in lower‐salinity continental or eutrophic environments. A significant distance‐decay pattern was noted for the T4‐like viral community, especially for those infecting cyanobacteria. Both deterministic and dispersal processes influenced viral community assembly, although environmental selection (e.g. temperature, salinity, bacterial abundance and community, etc.) had a greater impact than spatial distance. Network analysis confirmed the strong association between viral and bacterial community composition, and suggested a diverse ecological relationship (e.g. lysis, co‐infection or mutualistic) between and within viruses and their potential bacterial hosts.

Advances in research of the mid-deep South China Sea circulation - Dongxiao Wang; Qiang Wang; Shuqun Cai; Xiaodong Shang; Shiqiu Peng; Yeqiang Shu; Jingen Xiao; Xiaohui Xie; Zhiwei Zhang; Zhiqiang Liu; Jian Lan; Dake Chen; et al. (Science China Earth Sciences, 2019)

Novel phage–host interactions and evolution as revealed by a cyanomyovirus isolated from an estuarine environment - Yongle Xu; Rui Zhang; Nannan Wang; Lanlan Cai; Yigang Tong; Qiang Sun; Feng Chen; Nianzhi Jiao (Environmental Microbiology, 2018)
Summary Cyanophages are thought to affect the community structure, population dynamics, metabolic activity and evolution of picocyanobacteria and to impact the biogeochemical cycling in aquatic ecosystems. Here, we report an estuarine Synechococcus phage, S‐CBWM1, which represents a novel viral lineage and exhibits interesting genetic features related to phage–host interactions and evolution. S‐CBWM1 encapsidates four virion‐associated proteins related to cellular metabolic regulation. Several novel auxiliary metabolic genes related to multidrug efflux, cell wall and capsule synthesis or modifications were also identified. In addition, the presence of the largest number of tRNA genes hitherto found in a phage genome may contribute to the translation efficiency of unique genes. These genomic and proteomic features of S‐CBWM1 suggested phage–host interactions involved in adaptation to eutrophic estuarine environments. Phylogenetic and metagenomic analysis of the pol γ gene in the S‐CBWM1 genome provided new insights into the evolutionary path of mitochondrial DNA polymerase gamma. The S‐CBWM1 psbA contains two group I introns, representing the first instance of multiple introns within psbA from phage. The isolation of S‐CBWM1 reveals that estuarine ecosystems contain evolutionarily novel cyanophages that drive unique phage–host interactions.

Bioorganic fertilizer maintains a more stable soil microbiome than chemical fertilizer for monocropping - Feng Cai; Guan Pang; Rui-Xia Li; Rong Li; Xiao-Long Gu; Qi-Rong Shen; Wei Chen (Biology and Fertility of Soils, 2017)

A new biphenyl derivative from the mangrove endophytic fungus Phomopsis longicolla HL-2232 - Xiao-Bao Li; Guang-Ying Chen; Rui-Jie Liu; Cai-Juan Zheng; Xin-Ming Song; Chang-Ri Han (Natural Product Research, 2017)

Carboxyamidotriazole alleviates muscle atrophy in tumor-bearing mice by inhibiting NF-κB and activating SIRT1 - Chen Chen; Rui Ju; Lei Zhu; Juan Li; Wei Chen; De-chang Zhang; Cai-ying Ye; Lei Guo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2017)

Polyphasic characterisation of three novel species of Paraboeremia - Jia-Rui Jiang; Qian Chen; Lei Cai (Mycological Progress, 2017)

Chryseobacterium chengduensis sp. nov. isolated from the air of captive giant panda enclosures in Chengdu, China - Cai-fang Wen; Li-xin Xi; Shan Zhao; Zhong-xiang Hao; Lu Luo; Hong Liao; Zhen-rong Chen; Rong She; Guo-quan Han; San-jie Cao; Rui Wu; Qi-gui Yan; et al. (Journal of Zhejiang University-SCIENCE B, 2016)

Over-expression of StLCYb increases β-carotene accumulation in potato tubers - Xiao-yan Song; Wen-jiao Zhu; Rui-min Tang; Jing-hui Cai; Min Chen; Qing Yang (Plant Biotechnology Reports, 2016)

A new bibenzyl derivative with nuclear factor-kappaB inhibitory activity from Schefflera arboricola (Araliaceae) - Hang Li; Zi-Zhe Cai; Long-Ping Zhu; Xin-Jun Xu; Shao-Rui Chen; De-Po Yang; Zhi-Min Zhao (Natural Product Research, 2015)

Snail regulated by PKC/GSK-3β pathway is crucial for EGF-induced epithelial-mesenchymal transition (EMT) of cancer cells - Zong-cai Liu; Xiao-hui Chen; Hai-xing Song; Hong-sheng Wang; Ge Zhang; Hao Wang; Dan-yang Chen; Rui Fang; Hao Liu; Shao-hui Cai; Jun Du (Cell and Tissue Research, 2014)

Clinical Factors Associated With the Diagnosis and Progression of Diabetic Nephropathy - Shuang Liang; Qian Li; Han-Yu Zhu; Jian-Hui Zhou; Rui Ding; Xiang-Mei Chen; Guang-Yan Cai (Cell Biochemistry and Biophysics, 2014)

Erratum to: The Role of Autophagy Dysregulation in Manganese-Induced Dopaminergic Neurodegeneration - Jianbin Zhang; Rui Cao; Tongjian Cai; Michael Aschner; Fang Zhao; Ting Yao; Yaoming Chen; Zipeng Cao; Wenjing Luo; Jingyuan Chen (Neurotoxicity Research, 2014)

Benzene containing polyhydroxyalkanoates homo- and copolymers synthesized by genome edited Pseudomonas entomophila - Rui Shen; LongWei Cai; DeChuan Meng; LinPing Wu; Kai Guo; GuoXing Dong; Lei Liu; JinChun Chen; Qiong Wu; GuoQiang Chen (Science China Life Sciences, 2014)

The Role of Autophagy Dysregulation in Manganese-Induced Dopaminergic Neurodegeneration - Jianbin Zhang; Rui Cao; Tongjian Cai; Michael Aschner; Fang Zhao; Ting Yao; Yaoming Chen; Zipeng Cao; Wenjing Luo; Jingyuan Chen (Neurotoxicity Research, 2013)

Development of an immunochromatographic strip test for the rapid detection of okadaic acid in shellfish sample - Leqin Hu; Junxiu Liu; Qing Wang; Yang Zhang; Rui Jia; Chuner Cai; Weining Wu; Steven-Feng Chen; Peimin He (Journal of Applied Phycology, 2013)

Expression and functions of dopa decarboxylase in the silkworm, Bombyx mori was regulated by molting hormone - Mei-xian Wang; Zi-zheng Cai; Yan Lu; Hu-Hu Xin; Rui-ting Chen; Shuang Liang; Chabungbam Orville Singh; Jong-Nam Kim; Yan-shan Niu; Yun-gen Miao (Molecular Biology Reports, 2013)

Novel HMW glutenin genes from Aegilops tauschii and their unique structures - Wen-Jie Chen; Zhong-Wei Yuan; Lian-Quan Zhang; Xing Fan; Ze-Hong Yan; Ji-Rui Wang; You-Liang Zheng; Huai-Gang Zhang; Deng-Cai Liu (Genes & Genomics, 2012)

Analysis of 2,297 expressed sequence tags (ESTs) from a cDNA library of flax (Linum ustitatissimum L.) bark tissue - Song-Hua Long; Xin Deng; Yu-Fu Wang; Xiang Li; Rui-Qing Qiao; Cai-Sheng Qiu; Yuan Guo; Dong-Mei Hao; Wan-Qi Jia; Xin-Bo Chen (Molecular Biology Reports, 2012)

Gene expression profiling of Sinapis alba leaves under drought stress and rewatering growth conditions with Illumina deep sequencing - Cai-Hua Dong; Chen Li; Xiao-Hong Yan; Shun-Mou Huang; Jin-Yong Huang; Li-Jun Wang; Rui-Xing Guo; Guang-Yuan Lu; Xue-Kun Zhang; Xiao-Ping Fang; Wen-Hui Wei (Molecular Biology Reports, 2012)

Synthesis of (–)-arctigenin derivatives and their anticancer activity - Chen Gui-Rong; Cai Li-Ping; Dou De-Qiang; Kang Ting-Guo; Li Hong-Fu; Li Fu-Rui; Jiang Ning (Natural Product Research, 2012)

Localized Delivery of Antisense Oligonucleotides by Cationic Hydrogel Suppresses TNF-α Expression and Endotoxin-Induced Osteolysis - Lei Dong; Zhen Huang; Xing Cai; Jiawei Xiang; Yi-An Zhu; Rui Wang; Jiangning Chen; Junfeng Zhang (Pharmaceutical Research, 2011)

Molecular phylogeny of Ranunculaceae based on rbc L sequences - Ying-fan Cai; Sheng-wei Li; Min Chen; Ming-feng Jiang; Yi Liu; Yong-fang Xie; Quan Sun; Huai-zhong Jiang; Neng-wen Yin; Ling Wang; Rui Zhang; Cheng-lin Huang; et al. (Biologia, 2010)

Research development of the pathogenesis pathways for neuroschistosomiasis - Peng Wang; Ming-Can Wu; Shi-Jie Chen; Guo-Cai Luo; Xiang-Ling Cheng; Zhan-Sheng Zhu; Guang-Rui Zhao (Neuroscience Bulletin, 2010)

The research of air pollution based on spectral features in leaf surface of Ficus microcarpa in Guangzhou, China - Jie Wang; Ruisong Xu; Yueliang Ma; Li Miao; Rui Cai; Yu Chen (Environmental Monitoring and Assessment, 2008)